2011
DOI: 10.1111/j.1540-5826.2011.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Research on Ethnic Minority Students: 1995–2009

Abstract: Ethnic minority disproportionality has been a topic of extensive discussion and research for many years. In 1997, Artiles, Trent, and Kuan conducted a seminal review of the special education research literature to identify how often researchers report and disaggregate data in ways that would support conclusions about specific ethnic minority groups. These authors found alarmingly low rates of publication on identifiable minority groups. The purpose of this review is to replicate the work of Artiles et al. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…Comparable patterns have been documented for other, subsequent periods—1994 to 2012 (S. Trent et al, 2014) and 1995 to 2009 (Vasquez et al, 2011).…”
Section: The Protean Nature Of Disability Intersections and Fragmentamentioning
confidence: 58%
“…Comparable patterns have been documented for other, subsequent periods—1994 to 2012 (S. Trent et al, 2014) and 1995 to 2009 (Vasquez et al, 2011).…”
Section: The Protean Nature Of Disability Intersections and Fragmentamentioning
confidence: 58%
“…Also, consistent with the previous study that revealed the distinctive experiences of Caucasian girls and Latinas with their agent (Kim & Lim, 2013), the results of the current study shed light on ethnic-minority girls' unique challenge of double marginalization by both gender and ethnicity in ordinary mathematics classrooms, highlighting the need for further research on this group of students. In fact, there have been alarmingly few studies on culturally diverse students despite the growing proportion of these students in the current U.S. K-12 school population (Vasquez et al, 2011). Much remains to be clarified about the quality of these students' learning experiences in school mathematics.…”
Section: Discussionmentioning
confidence: 98%
“…Tal pesquisa marcaria um avanço importante na educação inclusiva, pois os pesquisadores documentaram durante décadas limitações substanciais nas estratégias de relato de amostra que têm implicações cruciais para a agregação dos resultados de pesquisa. Por exemplo, problemas foram observados na amostragem de alunos com dificuldades de aprendizagem (ARTILES; TRENT; KUAN, 1997;KEOGH et al, 1982;TRENT et al, 2014;VASQUEZ et al, 2011), estudos sobre a voz do estudante (GONZALEZ; HERNANDEZ-SACA; ARTILES, 2013), e estudantes de língua inglesa (ARTILES; KLINGNER, 2006;RAGAN;LESAUX, 2006).…”
Section: Interseções Nos Estados Fluidos De Deficiência: Um Novo Progunclassified